Validation of an Endometrial Tumor Diameter Model for Risk Assessment in the Absence of Lymph Node Mapping - McKayla J. Riggs (Journal of Patient-Centered Research and Reviews, 2020)
Purpose: This study aimed to assess the optimal tumor diameter for predicting lymphatic metastasis and to determine intraoperatively the need for lymph node dissection in patients with endometrioid endometrial cancer.